PROTECTION LAW FOR PUBLIC CUSTOMS : STUDIES ON IMPACT OF CORRIDOR MINING ACTIVITIES IN PAMPANG VILLAGE, SAMARINDA - Yuniarti Wijinarko; Aulia Vivi Yulianingrum; Elviandri (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Activity coal mining is one of the sectors who contributed towards national economic development, but in its implementation it often has an impact on the environment and society. is at in around region mining, including public customs. Wrong One regionWhich affected Pampang Cultural Village, Samarinda City, is an area of the Dayak Kenyah indigenous community and is located near the mining route of the coal transportation corridor. This study aims to analyze the forms of protection law against the indigenous people of Pampang Cultural Village based on applicable laws and regulations and analyzing the implementation of legal protection for indigenous people affected by activities mine corridor. Study This use method juridical empirical withapproach sociological Law. Data were obtained through interviews, field observations, and literature studies, which were then analyzed descriptively. qualitative. Results study show that in a way normative protection law to indigenous peoples has arrangedin Constitution Base Country Republic Indonesia Year 1945, Constitution Number 32 Years 2009 about Protection AndManagement Environment Life, as well as Constitution Number 3 Year 2020 about Mining Mineral And Coal. Form protectionlaw the includes protection Preventive measures include recognizing indigenous peoples' rights, access to information, and community participation, as well as repressive protection through complaint and dispute resolution mechanisms. However, the implementation of legal protection has not been optimal because communities still feel the impacts of corridor mining activities in the form of dust, increased heavy vehicle traffic, and disruptions to the environmental comfort and living spaces of indigenous communities. From a justice theory perspective, the legal protection provided has not been fully able to realize balance betweeninterest development economy And protection rights public customs. Therefore, it is necessary to strengthen government oversight, increase the participation of indigenous communities, and commit to company mining in carry out not quite enoughanswer social And environment use realizing effective and just legal protection.